The effects of different antiseptic mouthwash on microbiota around orthodontic mini-screw - Akbulut, Y. (Wolters Kluwer Medknow Publications, 2020)
Objective: This study aims to investigate the effects of different antiseptic mouthwash on microbiota around the mini-screw applied to patients undergoing fixed orthodontic treatment. Materials and Methods: From patients who have been undergoing fixed orthodontic treatment and who have mini-screws in their mouth, a total of 38 patients were selected for the study consisting of 4 groups, each of which has 15 mini-screws. The patients were selected from the following groups: no use of mouthwash (Group 1), use of 0.12% chlorhexidine gluconate-containing mouthwash (Group 2), use of essential oils-containing mouthwash (Group 3), and use of 7.5% povidone-iodine-containing mouthwash (Group 4). Plaque indices and gingival indices of the patients were measured at the beginning (T0) and at their appointments 3 weeks later (T1). In addition, biological samples were collected from the sulcus around the mini-screw with the help of sterile paper point. Results: The total number of microorganisms around the mini-screw in Group 2, Group 3, and Group 4 decreased significantly compared to Group 1. A significant decrease in Streptococcus oralis, Streptococcus mitis, Candida parapsilosis, total bacteria, plaque index, and gingival index count was observed in T1compared to T0. Conclusion: Antiseptic mouthwash in Group 2, Group 3, and Group 4 can be used to reduce the number of microbial microbiota around the mini-screw and to improve oral hygiene.
Keywords: Gingival index; microbiota; mouthwash; orthodontic mini-screw; periodontal index; plaque index